THE NEGATIVE IMPACTS OF MODERN SOCIAL MEDIA, AND WAYS TO TREAT THEM FROM AN ISLAMIC PERSPECTIVE - Dr.Adel Harb Basher (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Negative Impacts of Contemporary Social Media and How to Treat them from an Islamic Perspective. Allah Almighty has created human beings so that they socialize and communicate with one another. Methods of communication have developed with respect to time and place. Although the varied positive aspects of the social media are undeniable, the social media has become an overwhelming revolution that swept the moral values and principles in its way, and transgressed all criteria so that they became difficult to control. The social media is spreading atheistic thought and revolt against moral values. The social media is also contributing to the disintegration of Muslim families. It creates disorder in social relationships as it severs familial bonds and cordial ties among people. Therefore, it becomes an imperative to find a prescription to bring things back to their normal condition through a rightful Islamic approach that regularizes how to deal with the negative impacts of the social media so to convert them into useful ones, and hence serving both the community and the individuals